Lower trunk kinematics and muscle activity during different types of tennis serves - Chow John W; Park Soo-An; Tillman Mark D (BMC, 2009)
Abstract Background To better understand the underlying mechanisms involved in trunk motion during a tennis serve, this study aimed to examine the (1) relative motion of the middle and lower trunk and (2) lower trunk muscle activity during three different types of tennis serves - flat, topspin, and slice. Methods Tennis serves performed by 11 advanced (AV) and 8 advanced intermediate (AI) male tennis players were videorecorded with markers placed on the back of the subject used to estimate the anatomical joint (AJ) angles between the middle and lower trunk for four trunk motions (extension, left lateral flexion, and left and right twisting). Surface electromyographic (EMG) techniques were used to monitor the left and right rectus abdominis (LRA and RRA), external oblique (LEO and REO), internal oblique (LIO and RIO), and erector spinae (LES and RES). The maximal AJ angles for different trunk motions during a serve and the average EMG levels for different muscles during different phases (ascending and descending windup, acceleration, and follow-through) of a tennis serve were evaluated. Results The repeated measures Skill × Serve Type × Trunk Motion ANOVA for maximal AJ angle indicated no significant main effects for serve type or skill level. However, the AV group had significantly smaller extension (p = 0.018) and greater left lateral flexion (p = 0.038) angles than the AI group. The repeated measures Skill × Serve Type × Phase MANOVA revealed significant phase main effects in all muscles (p < 0.001) and the average EMG of the AV group for LRA was significantly higher than that of the AI group (p = 0.008). All muscles showed their highest EMG values during the acceleration phase. LRA and LEO muscles also exhibited high activations during the descending windup phase, and RES muscle was very active during the follow-through phase. Conclusion Subjects in the AI group may be more susceptible to back injury than the AV group because of the significantly greater trunk hyperextension, and relatively large lumbar spinal loads are expected during the acceleration phase because of the hyperextension posture and profound front-back and bilateral co-activations in lower trunk muscles.